Posthumane visioner: En postkønnet eller kvindelige cyberkultur? - Nina Lykke (The Royal Danish Library, 1999)
The article is a discussion of two cyberfeminists, Donna Haraway and Sadie Plant, and their innovative posthuman approaches to feminist decontruction of the masculine connotations of cyberculture. The author compares Haraway's cyborg-figure that represents a post-gender, post-origin and post-nature position to the alliance of women and machines, promoted by Plant, who, inspired by Luce Irigaray, attempts to inscribe an embodied feminine subject in cyberspace and trace a digital écriture féminine. In conclusion the article profiles the posthuman approaches of Haraway and Plant with the humanist critique of the social relations of gender, culture and technology, which is articulated in a "cyborg"-novel by Dorrit Willumsen "Programmeret til kærlighed" (Programmed to Love) (1981).